2013
DOI: 10.1002/jso.23442
|View full text |Cite
|
Sign up to set email alerts
|

Gastric outlet obstruction in gastric cancer: A comparison of three palliative methods

Abstract: In gastric cancer and GOO, the clinical condition of the patient before treatment affects survival and should be taken into account in determining the treatment. PR seems to provide a survival benefit and should be considered as treatment option for patients suitable for surgery. For patients unfit for surgery, ES provides rapid and efficient palliation. Chemotherapy also seems to improve survival in gastric cancer and GOO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
47
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 22 publications
(31 reference statements)
0
47
0
Order By: Relevance
“…[3][4][5][6][7] For patients with gastric cancer, surgical resection is not only the mainstay of radical treatment but also part of a multimodal therapeutic approach. [8][9][10] Postoperative complications may delay the initiation of postoperative treatment as well as lower patient quality of life. Tokunaga et al 11 have described the impact of postoperative abdominal complications on recurrence and overall survival in patients with gastric cancer.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7] For patients with gastric cancer, surgical resection is not only the mainstay of radical treatment but also part of a multimodal therapeutic approach. [8][9][10] Postoperative complications may delay the initiation of postoperative treatment as well as lower patient quality of life. Tokunaga et al 11 have described the impact of postoperative abdominal complications on recurrence and overall survival in patients with gastric cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Surgery is an important intervention in the treatment of gastric cancer with GOO [4], and the effects of this treatment are ideal, with symptom remission rates as high as 72% [9]. For patients undergoing surgery, pre-operative nutritional condition directly affects post-operative prognosis, overall survival, and disease-specific survival [10].…”
Section: Discussionmentioning
confidence: 99%
“…Often, coupled with this are long-term nutrient consumption problems, caused by most types of gastric cancer; thus, the vast majority of GOO patients have different degrees of malnutrition. Removal of the obstruction is the primary goal in the treatment of GOO patients, and the main method of treatment is surgery [4]. However, edema of the stomach and malnutrition lead to a decrease in the immune system, which increases the risk of peri-operative infection, poor healing of anastomotic and incision sites, and poor post-operative recovery, which also increases the risk of peri-operative pulmonary infection due to vomiting, causing aspiration into the lungs of patients with GOO [3].…”
Section: Introductionmentioning
confidence: 99%
“…However, in cases of tumor obstruction, we have three palliative methods to cure the quality of patients' life, such as non-surgical methods like pyloric stenting or bypass operation and surgical resection. Keränen et al [22] reported that the median symptom-free and overall survival were longest in the resection group than stenting or bypass operation. And, they concluded palliative resection followed by chemotherapy is important to prolong the patients' survival.…”
Section: Discussionmentioning
confidence: 99%